Soluble Serum CD81 Is Elevated in Patients with Chronic Hepatitis C and Correlates with Alanine Aminotransferase Serum Activity - Welker, Martin-Walter; Reichert, David; Susser, Simone; Sarrazin, Christoph; Martinez, Yolanda; Herrmann, Eva; Zeuzem, Stefan; Piiper, Albrecht; Kronenberger, Bernd (PLOS ONE, 2012)
Aim Cellular CD81 is a well characterized hepatitis C virus (HCV) entry factor, while the relevance of soluble exosomal CD81 in HCV pathogenesis is poorly defined. We performed a case-control study to investigate whether soluble CD81 in the exosomal serum fraction is associated with HCV replication and inflammatory activity. Patients and Methods Four cohorts were investigated, patients with chronic hepatitis C (n = 37), patients with chronic HCV infection and persistently normal ALT levels (n = 24), patients with long term sustained virologic response (SVR, n = 7), and healthy volunteers (n = 23). Concentration of soluble CD81 was assessed semi-quantitatively after differential centrifugation ranging from 200 g to 100,000 g in the fifth centrifugation fraction by immunoblotting and densitometry. Results Soluble CD81 was increased in patients with chronic hepatitis C compared to healthy subjects (p = 0.03) and cured patients (p = 0.017). Patients with chronic HCV infection and persistently normal ALT levels and patients with long term SVR had similar soluble CD81 levels as healthy controls (p>0.2). Overall, soluble CD81 levels were associated with ALT levels (r = 0.334, p = 0.016) and severe liver fibrosis (p = 0.027). Conclusion CD81 is increased in the exosomal serum fraction in patients with chronic hepatitis C and appears to be associated with inflammatory activity and severity of fibrosis.